La réforme druze dans les montagnes syriennes au ixe/xve siècle - Wissam Halabi-Halawi (Revue des Mondes Musulmans et de la Méditerranée)
In the 9th/15th century, a new kind of Druzism was reportedly formed by Emir al-Sayyid (m. 884/1479) in the Syrian mountains. Its foundations were long considered purely spiritual. However, through the reading of sources, a richer content and more ambitious stakes can be attributed to such an endeavor: al-Sayyid had a societal, religious and legal project imbued with strong ideology. The mountain area was nevertheless divided around this reform : the masters' followers were opposed to the local leaders who were close to the central authority. What seemed like deliverance for the poor proved to be a threat for the powerful. What some contemporaries considered Islamization was seen by others as the re-establishment of the original Druzism. Ultimately, al-Sayyid's reform included a political project that catered to the poorest among the rural community in a Syria that was experiencing an economic slowdown on the eve of the fall of the Mamluk regime.